Effect of surface species on Cu-TiO2 photocatalytic activity - Xin, Baifu; Wang, Peng; Ding, Dandan; Liu, Jia; Ren, Zhiyu; Fu, Honggang (Applied surface science, 2008)
The Cu-TiO2 nanoparticles with different Cu dopant content were prepared by sol-gel method. The structure of the as-prepared catalysts and the surface species of Cu-TiO2 were determined using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and diffuse reflection spectroscopy (DRS). The relationship between the photocatalytic activity and the surface species of Cu-TiO2 was revealed via the measurement of surface photovoltage spectroscopy (SPS) as well as the degradation of the rhodamine B (RhB). The experimental results suggest that the Cu-TiO2 photocatalysts with appropriate content of Cu (about 0.06mol%) possess abundant electronic trap, which effectively inhibits the recombination of photoinduced charge carriers, improving the photocatalytic activity of TiO2. While at high Cu dopant region ( > 0.06mol%), the excessive oxygen vacancies and Cu species can become the recombination centers of photoinduced electrons and holes. Meanwhile, at heavy Cu doping concentration, excessive P-type Cu2O can cover the surface of TiO2, which leads to decrease in the photocatalytic activity of photocatalyst. The photocatalytic experimental results are in good agreement with the conclusions of SPS measurements, indicating that there is a close relationship between the photocatalytic activity and the intensity of SPS spectra.